Student performance study: the outcomes of metabolic, molecular and physical-chemical characterization of intestinal tract microbiome on a four mammalian species model - Nataša CIBER; Tina ZUPANČIČ; Tamara ZORAN; Katarina ŠIMUNOVIĆ; Anja PUGELJ; Bojan PAPIĆ; Nika KLINEC; Andreja GAZVODA; Benjamin DRAKSLAR; Mateja DOLENC; Blaž STRES (Acta Agriculturae Slovenica)
Many environmental factors influence the structure of microbial communities, their activity and properties of the environment of the digestive tract. Contrary to constant disturbances, the system provides the basis for energy conversion and thus the long-term stable coexistence of different hosts and their specific intestinal microbiota over geological timescales. Since the methodological approaches proved to be the largest source of systematic errors in comparisons of microbial communities among different organisms of the same species or between different species, we tested a number of methods on samples from different species of mammals in order to verify the feasibility of this approach for future routine analysis of microbiomes:(i) analyses of physical-chemical parameters;(ii)the metabolic properties of attached, planktonic fractions in comparison to the total;(iii)structure of microbial communities of bacteria and archaea; (iv)data analysis. We used a model of intestinal samples from four species of mammals, encompassing the differences between the various types of intestinal tracts: ruminants and rodents (such as pre- and post- peptic fermentors), omnivores and carnivores. The second purpose of the study was to(i)assess the extent of spread of data due to the cooperation of the various operators on the data obtained, and(ii) to evaluate the skills of the students to carry out industry-oriented investigations and measurements in 1st year of MSc study Microbiology; and(iii) to promote awareness of the importance of routine laboratory work day and the corresponding duties. The results suggest(i)that the operators independently organized and shared tasks;(ii)successfully completed all methods;(iii)obtain relevant information;(iv)critically evaluated and interpreted within the extent of their knowledge;(v) that relative standard deviation(RSD) typically could be compared to those of the automated analytical procedures(<10 %) and therefore represented the maximum extent of the variability of the biological material itself. It follows that the motivated MSc students were able to uphold the unknown protocols under supervision and perform laboratory and analytical complex experimental task, process and interpret results, and approximate performance of analytical procedures in industrial laboratories to generate data sets of acceptable high-quality.